Resolution of Inheritance Disputes Through Non-Litigation in Kediri - Arifin, Zainal; Handayani, Emi Puasa (Faculty of Law, Kadiri Islamic University (UNISKA) Kediri, 2023)
Islamic law regulates anyone who is included as an heir who is entitled to receive and who is unentitled to receive an inheritance, in fact, there are Muslims who distribute the inheritance outside Islamic law. Positive Law also regulates the inheritance distribution which is settled through the courts. This study focuses on three questions, first is how to resolve inheritance disputes out-of-court according to positive law. The second is how the inheritance distribution implementation out-of-court is applied in Kediri. This research type conducted is mixed-legal-research that combines between normative and empirical. Normatively, this study will describe inheritance law concepts based on various works of literature and empirically it is a case study whose data is obtained directly from the society as the main source and through the reality that occurs in the society. This research can be investigated through interviews, namely data obtained directly from informants where the tools used in this interview method are interview guidelines to facilitate extracting information needed in the case to be studied. The data that has been obtained will be processed through several stages and analyzed descriptively and qualitatively by analyzing the research results concept with a review of Islamic law and positive law that applies to the disputes and conclude the research output